Місце норм адміністративного права в системі нормативно-правового регулювання медичного обслуговування членів сімей поліцейських в закладах охорони здоров’я МВС - Васьківський, О. П.; Vaskivskyi , O. P. (Науковий вісник публічного та приватного права. - 2021. - Вип. 6, т. 2. - С. 257-261, 2021)
Розкрито зміст, особливості та запропоновано власне визначення поняття нормативно-правового регулювання медичного обслуговування членів сімей поліцейських. Розглянуто систему нормативно-правових актів, які складають систему нормативно-правового регулювання медичного обслуговування членів сімей поліцейських в закладах охорони здоров’я МВС. Визначено місце та значення в межах нього норм адміністративної галузі права. Зроблено висновок, що система нормативно-правового регулювання медичного обслуговування членів сімей поліцейських в закладах охорони здоров’я МВС складається із великої кількості правових норм різної галузевої належності.

The relevance of the article lies in the fact that the study of the issue of medical care for family members of police officers requires the disclosure of various theoretical and legal issues, among which one of the most important is the issue of regulatory and legal regulation of this area. The study of the latter makes it possible to see the legal basis of medical care for these categories of subjects, as well as the basis for regulating the legal relations that arise. The degree of regulation and orderliness of social relations that arise in the process of providing medical services to family members of the National Police of Ukraine directly depends on high-quality, effective and meaningful legal regulation. The article reveals the content, features and offers a proper definition of the concept of regulatory and legal regulation of medical care for family members of police officers. The system of normative legal acts that make up the system of normative legal regulation of medical care for family members of police officers in health care institutions of the Ministry of Internal Affairs has been disclosed. The place and significance within it of the norms of the administrative branch of law have been determined. It was concluded that the system of regulatory and legal regulation of medical care for family members of police officers in health care institutions of the Ministry of Internal Affairs consists of a large number of legal norms of different branches. However, the key place among them belongs precisely to the norms of administrative law, which is confirmed by the fact that: a) with their help, the rights of family members of police officers to medical care in health care institutions of the Ministry of Internal Affairs of Ukraine are established; b) determine the legal status of subjects providing medical services; c) establish the order and conditions of medical care for family members of police officers in health care facilities of the Ministry of Internal Affairs; d) determine the administrative subordination between health care institutions and the Ministry of Internal Affairs, as well as the specifics of control and coordination of their work. In addition, the analysis of the provisions of the legislative acts makes it possible to state that there are a number of gaps and shortcomings in the relevant legal regulation that need to be resolved. At the same time, the specified problems are of both organizational and legal nature.

Раскрыты содержание, особенности и предложено собственное определение понятия нормативно-правового регулирования медицинского обслуживания членов семей полицейских. Рассмотрена система нормативно-правовых актов, составляющих систему нормативно-правового регулирования медицинского обслуживания членов семей полицейских в учреждениях здравоохранения МВД. Определены место и значение внутри него норм административной отрасли права.
The place of administrative law norms in the system of legal regulation of medical care for family members of police officers in health care institutions of the Ministry of Internal Affairs
Keywords: адміністративні норми; administrative norms; административные нормы; нормативно-правове регулювання; normative and legal regulation; нормативно-правовое регулирование; медичне обслуговування; health care; медицинское обслуживание; члени сімей поліцейських; members of policemen's families; члены семей полицейских; заклади охорони здоров’я МВС; health care institutions of the Ministry of Internal Affairs; заведения здравоохранения МВД